Simultaneous Determination of Sulfacetamide and Prednisolone by H-Point Standard Addition Method with Simultaneous Addition of Both Analytes in Some Biological Fluids - Hajian, R.; Fadaeian, M.; Ghanbari, F. (Asian Journal of Chemistry, 2010)
Simultaneous determination of sulfacetamide and prednisolone by UV-vis spectrophotometry and H-point standard addition method (HPSAM) with simultaneous addition of both analytes has described. The effect of various parameters including pH, wavelength selection and concentration ratio on the sensitivity and accuracy of method were investigated. The results of applying H-point standard addition method showed that sulfacetamide and prednisolone could be determined simultaneously with the concentration ratios of 1:6-10:1 in mixed samples, respectively. The method was applied to the simultaneous determination of sulfacetamide and prednisolone in some synthetic mixtures, plasma, whole blood and urine successfully.